Microcalorimetric Investigation of Water Vapor Adsorption on Silica Gel - Demir, Hasan; Mobedi, Moghtada; Demir, Hasan; Ülkü, Semra; Ülkü, Semra; Mobedi, Moghtada (Springer Verlag, 2011)
Water vapor adsorption on silica gel was investigated using Tian-Calvet-type microcalorimetry. Differential heat of adsorption data was obtained. The setup of microcalorimetry was used volumetric system to determine adsorption isotherms of water vapor-silica gel. The Langmuir model was used in the interpretation of the adsorption data. The Clausius-Clapeyron diagram was also given. Effective mass diffusivity of water vapor in the silica gel particle as a function of temperature was also determined. The silica gel, which was degassed under vacuum at 10 -7 mbar and 120 °C for 18 h, was found to adsorb 0.6, 0.98, 1.1, 1.4, 2, 3.5, 11, 13, and 14 wt% water vapor at 120, 110, 100, 90, 75, 60, 40, 35, and 30 °C, respectively. The diffusivities of water vapor inside the silica gel for short- and long-range periods were described using kinetics data as a function of temperature in the Arrhenius form.
Keywords: Diffusivity; Heat of adsorption; Microcalorimetry; Silica gel-water pair; Water vapor